Systemic immune-inflammation index associated with functional outcomes after endovascular thrombectomy in anterior circulation acute ischemic stroke - Han, Li; Miao, Tao; Zheng, Le-Yi; Hu, Xiao-Fei; Zhong, Jia-Wei (Frontiers in Neurology, 2025)
BackgroundMany patients undergoing endovascular thrombectomy (EVT) for anterior circulation acute ischemic stroke experience poor outcomes despite successful recanalization. The systemic immune-inflammation index (SII) integrates multiple inflammatory pathways. We aimed to evaluate the association between SII and clinical outcomes in anterior circulation stroke patients undergoing EVT.MethodsThis retrospective study included 741 consecutive patients who underwent EVT for anterior circulation stroke at a tertiary center between January 2021 and December 2024. SII was calculated as platelet count × neutrophil count/lymphocyte count within 24 h. The primary outcome was poor functional outcome (modified Rankin Scale 3–6) at 3 months. The safety endpoint was symptomatic intracranial hemorrhage (sICH). Associations were examined using multivariable logistic regression and cubic spline analyses.ResultsThe median SII was 1,247.9 [IQR: 804.9–2127.1]. Poor functional outcome occurred in 317 (42.8%) patients. After adjustment, log-transformed SII was independently associated with poor functional outcome (OR 1.428, 95% CI 1.159–1.759, P < 0.001). Patients in the highest SII tertile (>1,809) had significantly higher odds of poor outcome vs. lowest tertile ( ≤ 928.25) (OR 1.73, 95% CI 1.18–2.52, P = 0.005), with significant trend across tertiles (P for trend = 0.005). However, SII showed no association with symptomatic intracranial hemorrhage (OR 1.32, 95% CI 0.84–2.07, P = 0.235). The SII-outcome association was consistent across subgroups. Restricted cubic spline analysis confirmed a linear dose-response relationship (P for non-linearity = 0.173).ConclusionsIn anterior circulation stroke patients undergoing EVT, elevated SII is independently associated with poor functional outcome but not symptomatic hemorrhagic complications.